Family medicine board review - Waickus, Cynthia M.; Schwer, William A. (William Arthur); Plants, Scott H. (New York McGraw-Hill Professional, 2010)
Cardiovascular; Pulmonary; Gastrointestinal; Metabolic and Endocrine; Neurology...
Includes bibliographical references
Keywords: Family medicine -- Examinations, questions, etc; Y học